The council of mirrors / 9. - Buckley, Michael, 1969- (Sisters Grimm, 2012)
Hoping to save their family and the citizens of Ferryport Landing from the evil plans of Mirror, Sabrina and Daphne Grimm seek counsel from the other magic mirrors, who advise them to join forces with the Scarlet Hand.